Food and Nutrition Education: influence on students feeding behavior and nutritional status - Maria Irene de Castro Barbosa; Bárbara Ramos de Oliveira; Nágila Araújo de Carvalho; Karine Anusca Martins (O Mundo da Saúde, 2016)
The nutritional transition indicates inadequate food intake in our population and it requires the adoption of educational strategies in order to promote healthy behaviors. This study evaluated the influence of an educational intervention program in dietary habits and anthropometric indicators in elementary school students. This was a prospective quantitative study developed in a public school in Goiânia, Goiás, with 92 students. Sociodemographic characteristics were analyzed as well as weight, height and body mass index (BMI) measurements. In order to identify the feeding habits, the already validated Previous Day Food Quiz (PDFQ) was used. An educational intervention program was implemented and three activities were developed in each classroom. The students’ average age was 9.61 ± 1.17 years old, and the majority were girls (55.44%), social class “B” (54.38%); brown skin (57.90%); catholics (54.39%), living with their parents (68.42%) and they had one to two brothers (71.94%). Most participants had normal weight before and after the intervention, and 20.00% were overweight. After five months of the educational intervention, there was an increase in weight and BMI, although not statistically significant, and a significant height increase (p <0.0001). Fruits and vegetables consumed at lunchtime and during the afternoon snack increased, while it decreased at breakfast and dinnertime. The bean group intake at lunchtime decreased and increased at dinnertime. There was an increase in the consumption of unhealthy foods for breakfast and lunch. Food and nutrition education should be continuous and integrated into the pedagogical planning in order to achieve better results in school feeding behavior.